We don’t need more apps, we need connection: recommender systems as under-explored chance to promote students’ mental health at universities - Apolinário-Hagen, Jennifer; Schobel, Johannes; Helten, Anne-Kathrin; Sahan, Fatma; Pryss, Rüdiger; John, Dennis (Frontiers in Psychology, 2026)
Recent research indicates that more than one-third of university students globally experience substantial stress, mild anxiety symptoms, and mild or moderate–severe depressive symptoms, respectively. Despite the clear need, existing well-established mental health services (MHS) at universities, ranging from on-site health promotion programs to mobile health apps, are rarely used by students. Barriers for uptake include on the one hand person-specific factors, such as lack of problem awareness or knowledge about available services, and on the other hand challenges related to support structures like complex registration processes, limited resources or insufficient implementation of MHS. Low-threshold, personalized approaches could improve the accessibility, acceptance, and use of existing MHS. Recognizing this mismatch between student demand and service uptake, we propose a customizable recommender system for digital and traditional MHS provided or endorsed by universities. This Perspective article proposes the concept of “ConnectedHealth@University,” a planned platform solution designed to strengthen student mental health across academic settings, and to enhance the connection, reach, and effectiveness of available university services. The proposed platform will offer stress screening, personalized recommendations, and feedback mechanisms to optimize MHS. The overarching goal is to reduce access barriers by raising awareness for study-related stressors and better aligning services with student needs. The recommender system will guide students through a range of MHS at their universities, and provide tailored recommendations based on preferences, and stress profiles. Consequently, we suggest prioritizing recommender system development and the improvement of existing interventions over creating more that may remain underutilized.